2015
DOI: 10.1155/2015/569746
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fatty Acid Composition between Female and Male Japanese Quail Meats

Abstract: The objective of the present study was to compare the proximate analysis, fatty acids composition, omega fatty acids, trans fatty acids (TFAs), and ratio of the total poly unsaturated fatty acid (ΣPUFA) and total saturated fatty acid (ΣSFA) of female and male quail meats. Significant differences were not observed between pH, crude fat, moisture, and ash content of female and male quail meats (p>0.05). The male quail meat had higher fat and ash contents and lower moisture content than those of the female qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
7
16
0
Order By: Relevance
“…amount of total SFA compared to meat line quails (P<0.01), and particularly, a higher (P<0.01) proportions of lauric (C12:0; 2-fold higher), myristic (C14:0), palmitic (C16:0), heptadecanoic (C17:0) and stearic (C18:0) acids. The proportions of the single SFA found in the present study were consistent with those reported in literature on quails (Botsoglou et al, 2004;Genchev et al, 2008;Boni et al, 2010;Gecgel et al, 2015) and on chicken (Rule et al, 2002;Poureslami et al, 2010). The total monounsaturated fatty acids (MUFA) content, which in chickens is related either to the endogenous synthesis or to the gut absorption from the diet, was highest in meat-type quails (+ 11.5 p.p.…”
Section: Total Lipid Cholesterol Contents and Fatty Acid Compositionsupporting
confidence: 92%
See 3 more Smart Citations
“…amount of total SFA compared to meat line quails (P<0.01), and particularly, a higher (P<0.01) proportions of lauric (C12:0; 2-fold higher), myristic (C14:0), palmitic (C16:0), heptadecanoic (C17:0) and stearic (C18:0) acids. The proportions of the single SFA found in the present study were consistent with those reported in literature on quails (Botsoglou et al, 2004;Genchev et al, 2008;Boni et al, 2010;Gecgel et al, 2015) and on chicken (Rule et al, 2002;Poureslami et al, 2010). The total monounsaturated fatty acids (MUFA) content, which in chickens is related either to the endogenous synthesis or to the gut absorption from the diet, was highest in meat-type quails (+ 11.5 p.p.…”
Section: Total Lipid Cholesterol Contents and Fatty Acid Compositionsupporting
confidence: 92%
“…and C14:1 (P<0.05) acids; while, only the C20:1n-9 was higher (P<0.01) in egg line quails, even if contained at low weight percentages. The amount of total MUFA detected in meat line quails (51.5%) was similar to that reported by Gecgel et al (2015) for 56 day old male quails (48.72±3.27%); whereas, it was higher than that reported in Pharaoh breed (specialized for meat production) of 35 days old-40.7% (Genchev et al, 2008) and in spent quails of 8 months old-42.8% (Boni et al, 2010). Meat from egg-type quails had higher content of total PUFA (+4.5 p.p.…”
Section: Total Lipid Cholesterol Contents and Fatty Acid Compositionsupporting
confidence: 84%
See 2 more Smart Citations
“…The value and chemical composition of quail meat, which contains monounsaturated fatty acids at the amount of about 50%, polyunsaturated acids at the amount of 15%, and trans-confi gured acids at the amount of 3 % is known [1]. The unique composition of quail carcass products determines their nutritional and healing qualities.…”
Section: Introductionmentioning
confidence: 99%